The Influence of Affiliate Marketing on Millennial Tourists’ Intention To Visit Bali with Brand Trust as A Mediating Variable - Gede Febrian Govinda Tanjung; Hanugerah Kristiono Liestiandre; Ni Made Tirtawati (Eduvest - Journal of Universal Studies, 2026)
Digital marketing transformation has reshaped tourist decision-making, particularly among millennials who rely heavily on influencer-generated content. This study investigates the influence of affiliate marketing on millennials’ intention to visit Bali, with brand trust serving as a mediating variable. Adopting a quantitative approach, data were collected from 500 respondents who had never visited Bali but had been exposed to affiliate marketing content. Partial Least Squares Structural Equation Modeling (PLS-SEM) was employed for data analysis. The results indicate that affiliate marketing has a positive and significant direct effect on both brand trust and visit intention. Brand trust, in turn, significantly enhances visit intention and partially mediates the relationship between affiliate marketing and visit intention. The indirect effect through brand trust is stronger than the direct effect, underscoring the central role of trust in digital tourism marketing. These findings contribute to the digital marketing and tourism literature and offer actionable implications for destination managers seeking to design trust-oriented affiliate marketing strategies to attract millennial tourists to Bali.